THE USE OF COMPOSIT MATERIALS ALTERNATIVE FIBERGLASS (COCO FIBERS & RAGS) ON FIBERGLASS SHIP IN TRADITIONAL SHIPYARDS BENGKALIS REGENCY - Oni, Romadhoni (Department of Naval Architecture - Diponegoro University, 2015)
The limitations of the current wood raw material nowadays isÂ a threat to the traditional shipbuilding business. Besides the material is expensive, it is also about the difficulty in bringing the major raw materials, fiberglass, suchas wood fiber MAT and WR ( Woven Roofing). There is plan issues to ban on the use of the fiber within a certain periodÂ that accelerate the research in making the solution to be environment- free fiber. By doing the mechanical testing of coco fibre and rags, then gained streghth the bending and optimal impact and eligible BKI standard and ASTM D- 790 and ASTM D 638 and also the use of fiberglass reinforcement material fiber alternative is expected to save expenses in making that fiberglass. To reduce the environmental waste product that do not decompose in maintaining our health (avoiding toxic substances) against syntetic fiber. The result of bending test of composit and coir fabric is getting by using Bending Elasticity Modulus with average rags of hijab 12,88 Mpa, coco fibre 2,69 Mpa and fiber fabric undershirt 6, 57 Mpa, whereasÂ for testing the impact obtained average value of rags hijab 0,0808 kg/mm2 coco fibiers-0,16533 kg/mm2 and fiber fabric undershit 0, 00427 kg/mm2